α-Gal Nanoparticles in Wound and Burn Healing Acceleration - Galili, Uri (Adv Wound Care (New Rochelle), 2017)
Significance: Rapid recruitment and activation of macrophages may accelerate wound healing. Such accelerated healing was observed in wounds and burns of experimental animals treated with α-gal nanoparticles. Recent Advances: α-Gal nanoparticles present multiple α-gal epitopes (Galα1-3Galβ1-4GlcNAc-R). α-Gal nanoparticles applied to wounds bind anti-Gal (the most abundant antibody in humans) and generate chemotactic complement peptides, which rapidly recruit macrophages. Fc/Fc receptor interaction between anti-Gal coating the α-gal nanoparticles and recruited macrophages activates macrophages to produce cytokines that accelerate healing. α-Gal nanoparticles applied to burns and wounds in mice and pigs producing anti-Gal, decreased healing time by 40–60%. In mice, this accelerated healing avoided scar formation. α-Gal nanoparticle-treated wounds, in diabetic mice producing anti-Gal, healed within 12 days, whereas saline-treated wounds became chronic wounds. α-Gal nanoparticles are stable for years and may be applied dried, in suspension, aerosol, ointments, or within biodegradable materials. Critical Issues: α-Gal nanoparticle therapy can be evaluated only in mammalian models producing anti-Gal, including α1,3-galactosyltransferase knockout mice and pigs or Old World primates. Traditional experimental animal models synthesize α-gal epitopes and lack anti-Gal. Future Directions: Since anti-Gal is naturally produced in all humans, it is of interest to determine safety and efficacy of α-gal nanoparticles in accelerating wound and burn healing in healthy individuals and in patients with impaired wound healing such as diabetic patients and elderly individuals. In addition, efficacy of α-gal nanoparticle therapy should be studied in healing and regeneration of internal injuries such as surgical incisions, ischemic myocardium following myocardial infarction, and injured nerves.